ID 294 – Clinical and electroencephalographic features of patients with symptomatic epilepsy. Issue 3 (March 2016) - Ertaşoğlu Toydemir, H.; Bozkurt, D.; Azman, F.; Yurtsever, B.; Örnek, H.; Yayla, V.
Abstract : Objective: We aimed to evaluate the clinical and electroencephalographic features of symptomatic epilepsy (SE) patients. Method: A retrospective analysis was performed to 143 patients with SE attending to our epilepsy department between 2011 and 2014. Results: Mean age of 60F:83M patients was 32.2 ± 14.2 years. Neurological examination was unremarkable in 57.1% of the patients. The most common etiologic factor was trauma (41%). The seizure types were GTCS (52.4%), complex PS (47.6%), secondary GS (26.6%) and simple PS (23.8%). More than one seizure type was detected in 46% of them. EEG revealed pathologic patterns in 61.5% patients: Focal epileptogenic focus (56%), focal slowing (41%), generalized slowing (23%), generalized epileptogenic activity (15%) and nonspecific paroxysmal activity (10%). More than one type of pathologic EEG pattern was observed in 19% of the patients. Abnormalities on CT/MRI were detected in 74.8% of the patients. Conclusion: Although clinical and electroencephalographic findings of SE patients vary according to the underlying etiological factors, more than one type of seizure or pathological EEG pattern may be detected in the same patient. The management of SEs could be more complex than it seems. Key message: To draw attention to the variabilities in clinical and electroencephalographic findings of SE patients.